Effect of sulphur levels on four tropical grasses in "Cerrado" soils of "Mato Grosso do Sul", Brazil - Casagrande, José Carlos; Souza, Osni Correa de (Pesquisa Agropecuaria Brasileira, 2014)
A greenhouse experiment was conducted to evaluate responses of four tropical grasses, "gordura" (Melinis minutiflora cv. Cabelo de Negro) "Jarágua" (Hyparrhenia rufa), "braquiária" (Brachiaria decumbens australian type) and "satária" (Setaria anceps cv. kazungula) to five levels of sulphur (0, 15, 30, 45 and 60 kg/ha) in two "cerrado" Oxisols and one Entisol. Cuttings were done at 50, 95 and 150 days after plant emergency. Besides dry matter production visible symptoms of sulphur deficiency were observed through the experiment. Greater responses were associated with sulphur rates up to 30 kg/ha. Molasses grass and brachiaria were the most responsive species.